Atypical presentation of hamartomatous polyp mimicking a malignant tumor - Patricia Mulero-Soto; Maria Correa-Rivas; Anwar Abdul-Hadi (Journal of Pediatric Surgery Case Reports, 2023)
Polyps can be found throughout the intestine, but their presence in the small intestine is unusual. Hamartomatous polyps are seen in pathologies such as Peutz-Jeghers syndrome. We present a 17 year-old male with history of an incidental sigmoid polyp diagnosed as a neuroendocrine tumor, and later found with hamartomatous polyps mimicking a jejunal malignant tumor. To our knowledge, this is the first known case of a pediatric patient with this kind of presentation.